Experimental assessment of the performance of the PV/solar chimney under the cloudy weather - Firas Hussein Merie; Omer K. Ahmed (Results in Engineering, 2024)
One of the disadvantages of solar systems is their low efficiency due to weather conditions such as dust and clouds that reduce their performance. Therefore, this article examines the impact of cloudy weather on the performance of the PV/solar chimney to demonstrate the performance of these solar systems under overcast weather conditions. The PV/solar chimney system was designed and built, and two days in December were chosen for testing: 27 December with clear weather without clouds and 28 December with cloudy weather.The results showed that cloudy weather has a clear effect on the performance of the PV/solar chimney where the intensity of solar radiation is low. Clouds act as a barrier preventing access to sunlight, as the electrical power generated on a clear weather day reached 341.92 W, while on a cloudy weather day, 187.88 Watts at noon. The kinetic energy on a clear weather day reached 17.212 mW, while on a cloudy weather day, it reached 9.47 mW at noon. The electrical efficiency on a clear weather day reached 15.96 %. In contrast, on a cloudy weather day, it reached 13.2 % when the test started at 9 a.m., after which the efficiency decreased with the increase in the intensity of solar radiation to become 13.574 % in clear weather while 12.12 % in cloudy weather at noon, and the thermal efficiency on a clear weather day reached 56.06 %. In contrast, on a cloudy weather day, 42 % at noon. The total efficiency in clear weather reached 69.65 %, while on a clear weather day cloudy by 54.12 % at noon.